2022
DOI: 10.1099/mgen.0.000898
|View full text |Cite
|
Sign up to set email alerts
|

In silico investigation of the genus Campylobacter type VI secretion system reveals genetic diversity in organization and putative effectors

Abstract: Bacterial type VI secretion systems (T6SSs) are contractile nanomachines that deliver proteinic substrates into target prokaryotic or eukaryotic cells and the surrounding milieu. The genus Campylobacter encompasses 39 recognized species and 13 subspecies, with many belonging to a group known as ‘emerging Campylobacter pathogens’. Within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 91 publications
1
5
0
Order By: Relevance
“…Among them, proteins specifically associated with bacterial defense mechanisms, energy production and conversion, and cell wall biogenesis are noteworthy. In addition, we identified a key protein of the bacterial T6SS, VgrG, which is the puncturing spike of the machinery. This is in line with prevoius studies showing the ability of OMVs carriage of bacterial secretion system-associated proteins, however, in Helicobacter pylori …”
Section: Discussionsupporting
confidence: 81%
“…Among them, proteins specifically associated with bacterial defense mechanisms, energy production and conversion, and cell wall biogenesis are noteworthy. In addition, we identified a key protein of the bacterial T6SS, VgrG, which is the puncturing spike of the machinery. This is in line with prevoius studies showing the ability of OMVs carriage of bacterial secretion system-associated proteins, however, in Helicobacter pylori …”
Section: Discussionsupporting
confidence: 81%
“…and Robinson et al. and included the CC and ST of every C. jejuni strain from Chile sequenced to date ( van Vliet et al., 2021 ; Robinson et al., 2022 ). The analysis corroborated the global representation of CC-464, CC-353, CC-573, and CC-403 ( Figure 6A ).…”
Section: Resultsmentioning
confidence: 99%
“…A recent bioinformatic survey identified that Campylobacter T6SS gene clusters could be classified into three distinct cluster organizations (types I, II, and III). Analysis of T6SS genetic organization revealed that each of the T6SS gene clusters identified belonged to the T6SS group I-a, the same T6SS group as the T6SS of the Brazilian type strain 488 (Robinson et al, 2021;Robinson et al, 2022). In addition, we analyzed each ORF of the chromosomally encoded T6SS gene clusters in strains CFSAN122719 and CFSAN122739 and found a novel putative effector/immunity module (ORFs Z_00322 and Z_00323) in the variable region of the T6SS gene cluster of strain CFSAN122739 (Figure 6C).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the T6SS was shown to play a major role in bacterial inter-species competition, whereby T6SS-positive strains of C. jejuni outcompeted E. coli within the same niche [ 60 ]. While the Hcp has been characterised well as both a structural and effector protein in C. jejuni T6SS [ 57 ], very little is known about the roles of other effectors of the C. jejuni T6SS and their specific functions during infection, although recent bioinformatic studies have identified several putative T6SS effectors, including nucleases and an NAD + -glycohydrolase [ 61 , 62 ], which opens avenues for further investigation of their functions.…”
Section: Introductionmentioning
confidence: 99%